European Literature and Theology in the Twentieth Century
X, 191 p.
Keywords: The central themes of this collection of essays are the mystery of time past, present and future, and the problem of redemption. They are concerned with modern literature, with the threat of meaninglessness in the postmodern condition, and with the possibility of salvation. In an age of deferral and difference, this book addresses itself to eschatology and apocalypse, and redemption in, through, but particularly of, time itself. Hell and madness are never far away, yet the refiguration of time and the breaking in of the transcendent continue to suggest theological possibilities beyond the wastelands of the twentieth century. To those possibilities we look in hope.